On the effect of assessed returnable documents as active methodology in Power Electronics - Trujillo-Aguilera, Davinia; Pozo-Ruz, Ana; Sotorrío-Ruiz, Pedro Juan; Martí Campoy, Antonio; Blázquez-Parra, Elidia Beatriz (My University, 2015)
The methodological change caused by the implementation of the new degrees provides a clear opportunity to improve educational practices. This paper describes a teaching tool, named returnable document, to increase student work outside the classroom, motivate the students while raising their awareness about the importance and impact of their work. By using returnable documents teachers manage to strengthen the results of homework and the learning process in a flexible, motivating and entertaining way. In addition, compared to more traditional learning models, student participation is encouraged.
Keywords: Electrónica de potencia - Estudio y enseñanza; Continuous evaluation; Active methodology; Assessment; Teaching/Learning process; Power Electronics